Children in family contexts : perspectives on treatment - Combrinck-Graham, Lee (Guilford Press, 2006)
A practical guide to family-based therapy for childhood emotional and behavioral problems. This text presents assessment and treatment strategies that take into account children's developmental needs, different family forms, health and environmental challenges, and relationships with larger systems.